Parking Characteristics And Needs Study At Marga Traditional Market (International Journal of Environmental Sciences, 2025)
Marga Traditional Market is one of the markets in Tabanan Regency which is located in the Marga District. , is an activity of people engaged in the economy, especially traders. Marga Traditional Market is a place where the buying and selling process occurs, where most traders and buyers or people who come to Marga Traditional Market use transportation (vehicles) to get to the market, with these activities resulting in an increase in the volume of vehicles entering the Marga Traditional Market area due to the activities that occur, to anticipate this, adequate and neatly arranged parking facilities need to be provided so that they can provide the parking services desired by all parties. The purpose of this study was to determine the characteristics of parking at Marga Traditional Market and to determine whether the provision of parking space at Marga Traditional Market has met parking needs.The method used in data collection in this study is direct observation in the field by conducting a survey. The survey was conducted for 2 (two) days, namely on market days, namely Thursday, June 27, 2019, and Sunday, June 30, 2019. The study began from the start of routine market activities at 03.00 to 12.00 WITA.After conducting the research, the survey results then analyzed the parking volume, parking accumulation, average parking duration, parking turnover rate, parking capacity (parking supply), and parking index, then from the analysis the characteristics and parking needs at Marga Traditional Market can be known, the results of the data analysis obtained are that the volume of motorcycles is 768 vehicles, while for cars it is 325 vehicles. The highest parking accumulation for motorcycles occurred at 06.00-07.00 WITA, which was 153 vehicles, while for cars it occurred at 08.00-09.00 WITA, which was 47 vehicles. The average parking duration for motorcycles is 4.36 hours/vehicle, while for cars it is 4.22 hours/vehicle. The parking turnover rate for motorcycles is 0.74 vehicles/plot/hour, while for cars it is 0.89 vehicles/plot/hour. And the parking index for motorbikes is 6.32 while for cars it is 15.34, from the results of the research at the Marga Traditional Market, the parking needs for motorbikes and cars can no longer accommodate vehicles during market hours.